(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2023)
This research aims to analyze Jennifer Probst’s The Marriage Bargain from a Marxist perspective to examine how social institutions like marriage and human emotions are commodified in the era of late capitalism. The novel deals with the theme of love, romance and marriage, but also highlights the commodification of marriage in a capitalist society. The two main characters, Alexandria and Nicholas, use marriage as a means to solve their economic problems, challenging the traditional notion of marriage as a bonding of two souls. This research aims to explore this phenomenon. This qualitative study employs a Marxist literary analysis of the novel, focusing on the commodification of marriage and human emotions in the late capitalist society. It examines how the novel’s characters challenge the traditional concept of marriage and use it as a commodity to satisfy their material needs. The core finding of this research is that under the harsh economic pressures of late capitalism, human emotions and social institutions like marriage are commodified, and people compromise their ideals for economic gain. The novel shows how marriage is used as a commodity to solve economic problems, and how the traditional concept of marriage is being challenged by the utilitarian values of modern societies. The research concludes that The Marriage Bargain is an illustrative example of the commodification of marriage and human emotions in late capitalism. The exploration of this discourse clarifies how the institution of marriage is being used as a commodity to satisfy material needs. The novel raises an uncommon issue regarding the marital relationship, and the utilitarian attitude of its characters towards their own marriage represents the emerging social problem of the reification of human relationships.